SOCIAL AND PEDAGOGICAL DEVELOPMENT FACTORS OF TEACHER’S TUTORIAL ACTIVITY IN HIGHER EDUCATIONAL INSTITUTIONS - Mirsolieva, Mukhabbat; Giyasova, Umida; Sultanov, Anvar; Djuraev, Akbar (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The article touches upon the basic forms of tutorial activity in Higher Educational Institutions. The main forms of tutoring such as group and individual work has been described there. Special attention was paid for training as an element of group work, its aims and efficiency. Described psychological trainings are aimed to develop students’ professional confidence and self-awareness as well.